OVA66 promotes tumour angiogenesis and progression through enhancing autocrine VEGF-VEGFR2 signalling - Feifei Song; Qi Chen; Wei Rao; Renfeng Zhang; Ying Wang; Hailiang Ge; Qing Wei (EBioMedicine, 2019)
Background: Activation of autocrine VEGF-VEGFR2 signalling in tumour cells activates cell proliferation, survival, and angiogenesis, all of which are crucial for tumour progression. Ovarian cancer-associated antigen 66 (OVA66) is now known to be overexpressed in multiple tumours and plays a role in tumour development, but the underlying mechanisms has not been fully investigated. Methods: We employed ovarian and cervical cancer cells and mouse models to detect the role of OVA66 in angiogenesis, growth, and metastasis of cancer cells. Immunofluorescence and western blot were used to determine the function of OVA66 in regulating autocrine VEGF-VEGFR2 signalling. Immunohistochemistry and bioinformatics analysis were used to detect the correlation of OVA66 and VEGF expression. Findings: OVA66 overexpression in the cancer cell lines promoted VEGF secretion, tumour growth and angiogenesis in vitro and in vivo. Conversely, shRNA-mediated OVA66 knockdown had the opposite effects. Mechanistically, OVA66 overexpression was found to boost an autocrine VEGF–VEGFR2 positive-feedback signalling loop in the tumour cells, leading to amplified effect of VEGF on tumour angiogenesis and proliferation and increased migration in vitro and in vivo, respectively. Finally, we identified a significant positive correlation between the expression levels of OVA66 and VEGF in ovarian and cervical cancer specimens, and found that OVA66 was significantly associated with advanced ovarian cancer. Interpretation: We identify a novel function for OVA66 in regulating an autocrine VEGF–VEGFR2 feed-forward signalling loop that promotes tumour progression and angiogenesis. Fund: This work was supported by the National Natural Science Foundation of China (81602262); and Excellent Youth Scholar Program of Tongji University (2015KJ062). Keywords: OVA66, Tumour, VEGF, Autocrine, VEGFR2 signalling